2015
DOI: 10.1093/molbev/msv060
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Origin and Recent Innovations of RNA Polymerase IV and V

Abstract: Small RNA-mediated chromatin modification is a conserved feature of eukaryotes. In flowering plants, the short interfering (si)RNAs that direct transcriptional silencing are abundant and subfunctionalization has led to specialized machinery responsible for synthesis and action of these small RNAs. In particular, plants possess polymerase (Pol) IV and Pol V, multi-subunit homologs of the canonical DNA-dependent RNA Pol II, as well as specialized members of the RNA-dependent RNA Polymerase (RDR), Dicer-like (DCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 71 publications
6
94
1
Order By: Relevance
“…Arabidopsis has only one functional second largest subunit shared by both Pol IV and Pol V, but maize and other grasses have three (Haag et al, 2014;Huang et al, 2015). Consistent with genetic data showing diverse functions of more than one Pol IV holoenzyme , recent proteomic profiles support the presence of at least two Pol IV (Pol IVa and Pol IVb) and three Pol V (Pol Va, Pol Vb, and Pol Vc) subtypes in maize callus ( Fig.…”
Section: Diverse Roles For Multiple Dna-dependent Rna Polymerasessupporting
confidence: 75%
“…Arabidopsis has only one functional second largest subunit shared by both Pol IV and Pol V, but maize and other grasses have three (Haag et al, 2014;Huang et al, 2015). Consistent with genetic data showing diverse functions of more than one Pol IV holoenzyme , recent proteomic profiles support the presence of at least two Pol IV (Pol IVa and Pol IVb) and three Pol V (Pol Va, Pol Vb, and Pol Vc) subtypes in maize callus ( Fig.…”
Section: Diverse Roles For Multiple Dna-dependent Rna Polymerasessupporting
confidence: 75%
“…The Selaginella genome contains DCL3, RDR2, AGO4, and Pol IV/V largest subunit homologs (Banks et al, 2011), suggesting that the absence of 24-nucleotide RNAs in initial small RNA-seq libraries may be due to tissue-restricted expression. Phylogenetic analysis clearly identifies DCL3, AGO4, and Pol V-related homologs in basal plants (Huang et al, 2015). Finally, our previous analysis demonstrated that the P. patens DCL3 homolog is required for the accumulation of 22-, 23-, and 24-nucleotide RNAs from a handful of siRNA hot spots (Cho et al, 2008).…”
Section: Introductionmentioning
confidence: 70%
“…Dicers emerged early in the eukaryotic lineage and independently diverged in plants and animals (Mukherjee et al, 2013). Plants contain four ancient clades of DCL genes, with members in each clade being sub-functionalized for different types of small RNAs (Margis et al, 2006;Huang et al, 2015). P. patens has been reported to have no members of the DCL2 clade, single members of both the DCL3 and DCL4 clades, and two members of the DCL1 clade (Pp DCL1a and Pp DCL1b) (Axtell et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations led to the suggestion that, unlike phasiRNAs and miRNAs, hc-siRNAs were not universal features found in all land plants (Dolgosheina et al, 2008). However, homologs of key genes known to be responsible for hcsiRNA biogenesis and function in angiosperms clearly exist in diverse plant lineages (Zong et al, 2009;Banks et al, 2011;Huang et al, 2015;Wang and Ma, 2015;You et al, 2017). Reverse genetic analyses of these homologs, coupled with sRNA-seq analyses of the mutants, has shown that hc-siRNAs exist in the moss P. patens (Cho et al, 2008;Coruh et al, 2015), which implies that the pathway was most likely present in the last common ancestor of all land plants.…”
Section: Conservation Evolution and Annotations Of Endogenouse Sirnasmentioning
confidence: 99%